Control of communicable disease manual - Heymann, David L. (American Public Health Association, 2022)
The most widely recognized sourcebook on infectious diseases provides detailed, accurate, informative text for public health workers in official and voluntary health agencies, including those serving in the armed forces and other governmental agencies, and for all students of medicine. Each listing is easy to read and includes identification, infectious agent, occurrence, mode of transmission, incubation period, susceptibility and resistance. This 19th edition sticks to a tried and tested structure, but with every chapter updated by international experts at both CDC and WHO, priority has been given to ensuring global relevance New disease variants have been included and some chapters have been fundamentally reworked. The 19th edition is a timely update to a milestone reference work that ensures the relevance and usefulness to every public health professional around the world.